Unraveling the Darkness of Raja Ampat: A Neglected Criminal Justice System - Tjoetjoe Sandjaja Hernanto; Muhammad Fikri Alan; Mohammad Hazyar Arumbinang (Jurnal Dinamika Hukum, 2025)
This study examines the complex challenges confronting Raja Ampat, a globally significant region renowned its extraordinary marine biodiversity and rich cultural heritage, through the lens of an integrated criminal justice system. Raja Ampat is increasingly imperiled by illegal activities, including unregulated nickel mining and environmental exploitation, which threaten both ecological integrity and social well-being. Utilizing a normative legal methodology with statue and conceptual analysis, this research critically evaluates the current application of justice mechanisms involving law enforcement, judicial institutions, correctional services, and community participation. The study reveals critical systemic weaknesses, including fragmented legal authorities, poor coordination with local communities, and inadequate policy integration, that perpetuate illegal practices and social conflicts. Importantly, this study emphasizes the need to harmonize environmental regulations with criminal law frameworks to establish stronger deterrents against ecological crimes. Beyond its regional focus, this study contributes to the international discourse on ecological governance and criminal justice by providing a replicable model of integrated legal frameworks that balance ecological conservation with community empowerment. The findings provide actionable insights for global policymakers, law enforcement agencies, and civil society organizations seeking to enhance justice systems as effective instruments for sustainable development and social equity. Ultimately, this study advocates for a collaborative and comprehensive approach to justice system that aligns enforcement mechanisms with global sustainability goals, thereby supporting the preservation of biodiversity hotspots worldwide.